Decision influence and the link to internal modalities of delegations to conferences of the parties - Goodwin, Edward J. (Oxford University Press, 2018)
This paper concerns the likelihood that decisions adopted at plenary meetings of the parties to multilateral environmental agreements will influence the behaviour of States Parties. Relying upon a theory emphasising the importance of rational persuasion of decisions and the legitimacy of decision-making processes, the paper explains how choices concerning the preparation of delegates and then participation of delegations at plenary meetings of the parties to environmental treaties might enhance the likelihood of those decisions having a positive effect upon the actions of States Parties. This is done using a case study of the UK delegation to a recent meeting of the parties to the 1971 Ramsar Convention on Wetlands of International Importance. That case study also provides examples of potentially positive modalities adopted by the UK, whilst also revealing suspected concerns for the future surrounding retention of experienced delegates and the impact of Brexit.